THE USE OF SMARTPHONE AND LEARNING STRATEGIES IN AUTONOMOUS LEARNING - Nurhaeni Nurhaeni; Pupung Purnawarman (Indonesian EFL Journal, 2018)
Rapid penetration of smartphone in students’ life currently leads to the extreme influence and addiction of smartphone use in their daily activities (Alexander, 2011; Hough, 2011). Later on, it raises concern about the negative impact of smartphone use towards students’ learning performance and achievement (Kibona Mgaya, 2015). On the other hand, several studies found that smartphone is a possible learning tool that can be utilized by students to learn on their own, or autonomously (Kim Kwon, 2012; White Mills, 2014; Woodcock, Middleton, Nortcliffe, 2012). Hence, the purpose of this research was to investigate whether or not the smartphone use can influence students’ autonomous learning strategies. Both smartphone and autonomous learning share similar principle of independence based on their traits, such as taking control in learning and individuality. The students of Islamic Economy Department that currently enrolled in English class were chosen as the sample of this research. Correlational study was applied with further regression analysis conducted on the collected data. The instruments used in this research were questionnaires and interview. The findings revealed that the use of smartphone influence students’ learning strategies. Furthermore, cognitive and social/affective strategies are the strategies that were influenced the most and metacognitive strategies were influenced the least by the use of smartphone in learning English.Keywords: autonomous learning, learning strategies, smartphone use